The effect of training in capoeira in the agility and flexibility in adolescents males - Mazini Filho, Mauro Lúcio (2013)
Introduction: Capoeira is a Brazilian sport with its history rooted in a lot of rhythm, dance, fights, interventions political and popular. As sport is anexcellent way to improve fitness in general. Objective: to prove that the regular practice of this sport by individuals adolescent males, would benefit the valences physical agility a flexibility. Methods: for this we used the agility test “Shuttle Run” and flexibility sit and reach with the help of the bank of Wells, before and after 14 weeks of training in Capoeira twice times a week with participation of adolescents (Experimental Group). Also were applied together the same tests on 10 male students (Control Group) in response to physical education classes and non-practice in Capoeira, to find the effectiveness of results. Results: were found in the agility test in the comparison group (score=0.14). In comparison within groups, the EG had a score of 0,005 and CG had a score of 0.21. In return for the flexibility test comparing between groups the result was not satisfactory(score = 0.59). But compared the results of pre-test and post-test in the experimental group only flexibility we see an improvementfrom an average of 38.84±7.46 cm to 42.71±7.88 cm. Conclusion: was that fourteen weeks of training capoeira improves agility and capoeira keeps the existing level of flexibility.